Intrasexual aggression reduces mating success in field crickets - Eleanor K. Tinsley; Nathan W. Bailey (Ecology and Evolution, 2023)
Abstract Aggressive behaviour is thought to have significant consequences for fitness, sexual selection and the evolution of social interactions, but studies measuring its expression across successive encounters—both intra‐ and intersexual—are limited. We used the field cricket Teleogryllus oceanicus to evaluate factors affecting repeatability of male aggression and its association with mating success. We quantified focal male aggression expressed towards partners and received from partners in three successive, paired trials, each involving a different male partner. We then measured a proxy of focal male fitness in mating trials with females. The likelihood and extent of aggressive behaviour varied across trials, but repeatability was negligible, and we found no evidence that patterns of focal aggression resulted from interacting partner identity or prior experience. Males who consistently experienced aggression in previous trials showed decreased male mating ‘efficiency’—determined by the number of females a male encountered before successfully mating, but the effect was weak and we found no other evidence that intrasexual aggression was associated with later mating success. During mating trials, however, we observed unexpected male aggression towards females, and this was associated with markedly decreased male mating efficiency and success. Our findings suggest that nonadaptive aggressive spillover in intersexual mating contexts could be an important but underappreciated factor influencing the evolution of intrasexual aggression.